Learning Greetings Made Fun: Developing Gamified E-Learning Media with PowerPoint - A. Nidaan Khafiatun Syahrah; Arifuddin Arifuddin; Nur Fakhrunnisaa; Inrawati Inrawati (Educational Journal of Learning Technology, 2026)
This research aims to develop PowerPoint-based Gamified E-Learning media on greeting material in the Islamic Religious Education class IV SDIT Darul Khaerat Padang Sappa. The research uses the Research and Development (R&D) method with the ADDIE development model, which includes the Analyze, Design, Development, Implementation, and Evaluation stages. The subjects of the study were 15 grade IV students and 1 Islamic Religious Education teacher. Data collection was carried out through observations, interviews, validation sheets, practicality questionnaires, and learning motivation questionnaires. The results of the study showed: (1) media validity reached 75% (valid) from media experts and 95.8% (very valid) from material experts, an average of 85.4%; (2) the practicality test obtained 91.7% from teachers and 87.1% from students (very practical, average 89.4%); (3) the effectiveness test showed an increase in learning motivation from 69.02% (pre-treatment) to 88.1% (post-treatment) with an N-Gain value of 0.616 (medium category). The final prototype is a PowerPoint-based interactive learning medium that integrates VBA features with gamification elements, including alphabetical games, interactive quizzes, and an automatic scoring system.